1991
DOI: 10.1093/ajcn/54.5.788
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of the components of energy balance in well-nourished lactating women

Abstract: The mechanisms by which well-nourished women meet the additional energy costs of lactation were studied by measuring energy intake (EI), basal metabolic rate (BMR), total energy expenditure by doubly labeled water (TEE), physical activity plus thermogenesis (TEE-BMR), changes in body fat stores, and milk energy transfer. Ten women were studied at 36 wk gestation; 4, 8, and 12 wk lactation (L4, L8, L12); and when nonpregnant and nonlactating (NPNL) after weaning. At L4, L8, and L12 the energy transferred in mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 17 publications
5
95
0
Order By: Relevance
“…Alternatively, the differences observed were small enough that sample sizes of n ¼ 229 for both LACT and NPNL women would be required to show a significance at 80% power. This finding of a non-significant tendency for BMR to be higher in lactating women is in agreement with the majority of studies in both developing (Schutz et al, 1980;Singh et al, 1989;Guillermo-Tuazon et al, 1992;Madhavapeddi & Rao, 1992), and developed countries (Goldberg et al, 1991;Illingworth et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, the differences observed were small enough that sample sizes of n ¼ 229 for both LACT and NPNL women would be required to show a significance at 80% power. This finding of a non-significant tendency for BMR to be higher in lactating women is in agreement with the majority of studies in both developing (Schutz et al, 1980;Singh et al, 1989;Guillermo-Tuazon et al, 1992;Madhavapeddi & Rao, 1992), and developed countries (Goldberg et al, 1991;Illingworth et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have found a weight loss, corresponding to a fat mass reduction (Forsum et al, 1992;Motil et al, 1998;Butte et al, 1999), and others no change (van Raaij et al, 1990;Goldberg et al, 1991;Lovelady et al, 1995), because of increased energy intake to compensate for lactation. In the present study the women lost weight between 3.5 and 5.5 months postpartum, most of which was fat-free mass, but there was also a reduction in suprailiac skinfold thicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attention has focussed on lactating women and a number of studies have investigated their energy expenditure and body composition (Goldberg et al, 1991;Adair & Popkin, 1992;Forsum et al, 1992;Guillermo-Tuazon et al, 1992;Piers et al, 1995;Dewey, 1998;Butte et al, 1997Butte et al, ,1999Krebs et al, 1997;Motil et al, 1998;Spurr et al, 1998). However there have been few longitudinal studies beyond 6 months post-partum (cf Lawrence et al, 1986) and most of the subjects were well-nourished mothers (van Raaij et al, 1990;Adair & Popkin, 1992;Motil et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…DH (Goldberg et al, 1991b) 10 mothers 26 ± 40 Volunteers in response to advertisements. Measured post-lactation.…”
Section: Appendixmentioning
confidence: 99%